IMPROVING THE WEAR RESISTANCE OF POLYVINYL CHLORIDE SURFACE BY USING THE FRICTION STIR PROCESSING TECHNIQUE - Abdullah, Sajid Abdullah; Abdulkadhum, Dr Hazim H.; Hamza, Sanaa (Journal of Applied Engineering Science, 2023)
Friction Stir Processing is considered one of the essential methods for improving the surfaces of polymeric materials by adding reinforcing particles in specific ratios to form a composite material with better surface properties than the properties of the base material. The Friction Stir Processing technique was employed in the present investigation to introduce graphite particles onto the polyvinyl chloride surface. Various volumetric ratios of 5, 8, 11, 14, 17, and 20% were used for the incorporation of graphite particles. Mechanical tests (flexural strength, hardness, and wear resistance) were carried out. The experiments demonstrated a noteworthy enhancement in the measured characteristics, with the most notable outcomes observed when the graphite content was increased by 20%. Consequently, this investigation determined that applying the Friction Stir Processing technique effectively reinforced the polyvinyl chloride surface by forming a successful surface composite.
Keywords: friction stir processing, composite materials, polyvinyl chloride, graphite particles, mechanical properties